The influence of communication, organizational commitment, and work-life balance on employee performance - Siti Hamidah; Nasution Nasution (Jurnal Mantik, 2023)
Employee performance within hospitals can be impacted by several factors, including knowledge, motivation, and the working environment. Numerous studies emphasize strategies for enhancing employee performance in healthcare settings, such as training and development initiatives and fostering better communication and collaboration between different departments. This particular study seeks to assess the impact of communication, organizational commitment, and work-life balance on the performance of employees at Bhayangkara Hospital in Bengkulu City. The research employs a quantitative approach, with the study population comprising Bhayangkara Hospital employees, and a sample size of 170 respondents. The data analysis employs structural equation modeling (SEM) through the Partial Least Square (PLS) program. The findings of the research reveal that communication (X1), organizational commitment (X2), and work-life balance (X3) collectively influence employee performance (Y). Through calculations, it is established that the combined contribution of communication variables (X1), organizational commitment (X2), and work-life balance (X3) to employee performance (Y) is 33.7%, leaving 66.3% influenced by unexplored factors not covered in this study